(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Singapore is one of the leading countries in digitalization and blockchain technology. Since 2016, Singapore has implemented the Ubin project to create a national digital currency. In 2019, Singapore passed the Payment Services Act. The paper aims to analyze Singapore’s legislation and MAS policies and identify approaches that can be used to improve legislation in other states. To meet that aim, the general scientific techniques and methods of scientific cognition, such as analysis, synthesis, deduction, induction, system-structural and formal-logical approaches are utilised. Based on the analysis, it is concluded that Singapore extends the provisions of securities legislation to digital tokens, which have the characteristics of securities or futures. Digital tokens, which are cryptocurrencies, are regulated by the Payment Services Act containing criteria to distinguish payment tokens from other virtual objects. Using this approach minimizes difficulties in regulating the circulation of, for example, bitcoins. In addition, MAS has developed a set of rules enshrining requirements for cryptocurrency exchanges, which reduces the risks of fraud and money laundering using cryptocurrencies. The paper also analyses MAS reports on developing a state’s digital currency. The paper concludes that other states can use Singapore’s experience to shape or modernize their legislation.